Perbandingan Parameter Mutu Ekstrak Bunga Telang (Clitoria ternatea) Menggunakan Metode Refluks, Sokhlet, dan Maserasi - Hairiyah, Nina; Amalia, Raden Rizki; Nuryati, Nuryati; Faridah, Faridah (Jurnal Teknologi Agro-Industri, 2023)
Butterfly pea flower (Clitoria ternatea) is a plant that is known to contain high levels of flavonoids, anthocyanins and antioxidants which can be used for food and non-food products. Butterfly flower extract can be used as an active ingredient in product manufacturing. This research aims to compare the quality parameters of pea flower extract (Clitoria ternatea) obtained using the reflux, sochlet and maceration methods from organoleptic, yield, water content, total ash content, acid insoluble ash content and flavonoid aspects. The research results showed that for organoleptic parameters, butterfly pea flower extract had a deep purplish blue color and a distinctive aroma of butterfly pea flower. Based on the parameters of yield value, water content, total ash content, acid insoluble ash content, and flavonoids, the best extraction method for pea flowers (Clitoria ternatea) is the heat method (reflux or sokhlet).